The utility of a genetic kidney disease clinic employing a broad range of genomic testing platforms: experience of the Irish Kidney Gene Project - Elhassan, Elhussein A E; Murray, Susan L; Connaughton, Dervla M; Kennedy, Claire; Cormican, Sarah; Cowhig, Cliona; Stapleton, Caragh; Little, Mark A; Kidd, Kendrah; Bleyer, Anthony J; Živná, Martina; Kmoch, Stanislav; et al. (JN. Journal of nephrology, 2022)
BACKGROUND AND AIMS: Genetic testing presents a unique opportunity for diagnosis and management of genetic kidney diseases (GKD). Here, we describe the clinical utility and valuable impact of a specialized GKD clinic, which uses a variety of genomic sequencing strategies. METHODS: In this prospective cohort study, we undertook genetic testing in adults with suspected GKD according to prespecified criteria. Over 7 years, patients were referred from tertiary centres across Ireland to an academic medical centre as part of the Irish Kidney Gene Project. RESULTS: Among 677 patients, the mean age was of 37.2 ± 13 years, and 73.9% of the patients had family history of chronic kidney disease (CKD). We achieved a molecular diagnostic rate of 50.9%. Four genes accounted for more than 70% of identified pathogenic variants: PKD1 and PKD2 (n = 186, 53.4%), MUC1 (8.9%), and COL4A5 (8.3%). In 162 patients with a genetic diagnosis, excluding PKD1/PKD2, the a priori diagnosis was confirmed in 58% and in 13% the diagnosis was reclassified. A genetic diagnosis was established in 22 (29.7%) patients with CKD of uncertain aetiology. Based on genetic testing, a diagnostic kidney biopsy was unnecessary in 13 (8%) patients. Presence of family history of CKD and the underlying a priori diagnosis were independent predictors (P < 0.001) of a positive genetic diagnosis. CONCLUSIONS: A dedicated GKD clinic is a valuable resource, and its implementation of various genomic strategies has resulted in a direct, demonstrable clinical and therapeutic benefits to affected patients.
Keywords: genetické testování; polycystické ledviny autozomálně dominantní; Renal Insufficiency, Chronic; chronická renální insuficience; kationtové kanály TRPP; TRPP Cation Channels; Middle Aged; mutace; Prospective Studies; Adult; mladý dospělý; Young Adult; Mutation; Humans; prospektivní studie; ledviny; lidé středního věku; Polycystic Kidney, Autosomal Dominant; dospělí; Kidney; Genetic Testing; lidé